Centro de carreiras como elementos estratégicos das instituições de ensino superior - Pantaroto, Raphael (2023)
Workers must be able to deal with uncertainty in an increasingly unpredictable career environment. In this context of major transformations, Higher Education Institutions (HEIs) play a fundamental role in preparing students so that they can build a solid career. To assist HEIs in this mission, Career Centers (CC) are becoming increasingly important. This scenario gave rise to this study, which aims to identify how the career center can contribute to the strategy of higher education institutions to improve the formation of students and their careers. Regarding the methodology, this work is qualitative and multiple case studies were used. Data collection was done through documentary research and semi-structured interviews with managers from career centers at three universities abroad; data analysis was done through reduction, display and verification according to the precepts of Miles and Huberman (1994). As main results and contributions, the study evaluated in depth three HEI career centers abroad. This made it possible to identify the strategic role of these centers, understand the resources related to them, analyze the scope of these centers and relate them to the concept of employability and, finally, propose a structure for career centers that can be used partially or entirely by managers of HEIs and career centers in Brazil.